2000
DOI: 10.1177/136140960000500505
|View full text |Cite
|
Sign up to set email alerts
|

Violent incidents in a forensic adolescent unit: A functional analysis

Abstract: This paper reports on a survey which identified categorised and measured the relative frequency of specific antecedents before, and the consequences following, violent incidents in an adolescent forensic unit during a two-year period. Retrospective analysis of 219 violent incidents involved the examination of incident forms, nursing-process records and accident reports. Antecedents and precipitating factors were also recorded. The results demonstrated that the vast majority of incidents were precipitated by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 35 publications
2
11
1
Order By: Relevance
“…2004). However, in his UK‐based study of violence in forensic psychiatric care, McDougall (2000) found adolescents with a diagnosis of schizophrenia were overrepresented in the group of service users who were aggressive. Another study found that over a 12‐month period, 66.7% of hospitalized adolescents with psychosis exhibited violent behaviour (Inamdar et al .…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…2004). However, in his UK‐based study of violence in forensic psychiatric care, McDougall (2000) found adolescents with a diagnosis of schizophrenia were overrepresented in the group of service users who were aggressive. Another study found that over a 12‐month period, 66.7% of hospitalized adolescents with psychosis exhibited violent behaviour (Inamdar et al .…”
Section: Introductionmentioning
confidence: 99%
“…2001; Fritsch et al . 1992; Gabel & Shindledecker 1991; McDougall 2000). This is not surprising, given that a history of aggression is a diagnostic criterion for the disorder (American Psychiatric Association 2000; Barton et al .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations